Fiscal policy, economic growth and innovation: An empirical analysis of G20 countries - Horst Hanusch; Lekha S. Chakraborty; Swati Khurana (Levy Economics Institute of Bard College, 2017)
This paper analyzes the effectiveness of public expenditures on economic growth within the analytical framework of comprehensive Neo-Schumpeterian economics. Using a fixed-effects model for G20 countries, the paper investigates the links between the specific categories of public expenditures and economic growth, captured in human capital formation, defense, infrastructure development, and technological innovation. The results reveal that the impact of innovation-related spending on economic growth is much higher than that of the other macro variables. Data for the study was drawn from the International Monetary Fund's Government Finance Statistics database, infrastructure reports for the G20 countries, and the World Development Indicators issued by the World Bank.
Keywords: H5; O30; O38; 330; Fiscal Policy; Public Expenditure; Defense; Innovation; Growth; Neo-Schumpeterian Economics